Design and experimental analysis of heat-driven ejector refrigeration system - Redo, Mark Anthony B. (2014)
Ejector refrigeration system utilizes low-grade thermal energy mainly from renewable sources and industrial waste heat to produce cooling without using the power consuming compressor of the conventional refrigeration system. Natural refrigerants can be harnessed without ozone depleting and global warning potentials. Thus, it offers solution in reducing electricity demand and environment problems. It has also great market potential because of its structural simplicity with no moving parts, making it robust, long lifespan and low initial and maintenance costs. Mathematical modeling was established by employing principles of thermodynamics and conservation equations to control volumes of ejector components such as nozzle, pre-mixing section, mixing chamber and diffuser. R134a was set as the working fluid with good thermodynamic properties, non-corrosive, non-toxic, and non-flammable. Simulations were conducted and found out that the generating and condensing temperatures have a great effect on the system performance. Optimized ejector geometry was projected for given set of working conditions like generating,condensing and evaporating temparatures of 95 degree celcius, 40 degree celcius and 10 degree celcius respectively. After yielding numerical results, experiment rig was built for validation. Main components such as boiler, vapor generator, condenser, evaporator, pump, expansion device and ejector were designed, fabricated and installed in reference to the operating parameters. Performance data acquisition was done by placing pressure transducers, thermocouples and flow meters om important test points. The results were recorded at steady state condition. Experimental data showed good agreement with mathematical results where very small variances were attained. An average relative error of 5.3% for entertainment ratio, cooling effect and COP was obtained. When the generating temperature was varied, the performance of the system was greatly affected because the optimized ejector geometry perfectly works on a set of working conditions. When the ERS is compared to the conventional vapor compression refrigeration system in terms of economic aspect. the previous is competitive with smaller cumulative cost.